Croatia : Background Notes and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1994)
This Background Notes paper and Statistical Appendix presents a summary of the Croatian Tax System as of August 1994. The paper discusses the experience with incomes policies in Croatia. It highlights that incomes policy has played an important role in the Croatian stabilization program as the government has pursued the twofold objective of limiting costs in the public sector and of curbing the wage-price spiral. The paper briefly reviews developments in incomes policy and recent developments in real wages. It also describes the social safety net in Croatia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet